Pentecostalism and Development: The Role and Prospects of Prosperity Gospel in the Socio-Economic Development of Nigeria - Asuquo, Offiong Offiong (Program Studi Sosiologi, 2020)
The prosperity gospel is a popular doctrine that is taught and practised by many Pentecostal churches in Nigeria. It has enhanced and improved the financial status of many Pentecostal churches thereby enabling them to carry out several projects which have enhanced the socio-economic wellbeing of many people. Such projects include the establishment of schools, universities, printing presses, financial empowerment of members, provision of welfare packages and care for the needy. This paper highlights the meanings of Pentecostalism, prosperity gospel and development. It also attempts to explain how prosperity gospel, in the context of some Pentecostal churches- Living Faith Church (Winners Chapel) and Christian Central Chapel International, among others, have contributed to the socio-economic wellbeing of many. However, this paper acknowledges that there is room for an improvement and expansion of the contributions of prosperity gospel to development in the future. Hence suggestions are given on how to harness, improve and expand the benefits of the prosperity gospel in Nigerian society in the future.